Reconceptualizing professional growth: Biology teachers’ evaluation of a professional development program - Jleian Mard M. Loseñara (JPBI (Jurnal Pendidikan Biologi Indonesia))
Teacher professional development (TPD) programs enhance teachers' skills and competence. Since teachers are the primary beneficiaries, their perceptions are crucial in assessing TPD effectiveness and relevance, providing insights to improve future program design and evaluation. This study focused on Biology teachers, who were non-education graduates, and their evaluation of a need-based TPD program. Using a mixed-methods approach, the study explored their experiences and learning outcomes from their participation in the TPD. The quantitative findings revealed that the teachers rated the TPD program as highly effective. Furthermore, the qualitative data indicated that teachers perceived the TPD as highly beneficial, particularly in enhancing their ability to integrate technology and updated content into their lessons. This aligns with King’s framework, which emphasizes the importance of context-responsive and reflective PD for sustained professional growth. Teachers suggested that revising the program flow to include breaks, addressing technology-related concerns like mobile-friendly and free technologies, and expanding the training's coverage to include additional Biology content and more Biology teachers could improve the TPD. The program's effectiveness was further evidenced through teaching artifacts, such as instructional materials, lesson plans, and recorded teaching videos, which reflected the teachers' application of their learning.